PENGARUH DESENTRALISASI, KETIDAKPASTIAN TUGAS, DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL DENGAN SISTEM AKUNTANSI MANAJEMEN SEBAGAI VARIABEL MODERASI - Nurkholik, Nurkholik; Paramita, P.D. (LPPM Universitas Ibnu Sina, 2025)
Abstract This research is motivated by the problems encountered at PT. Real Glass, a dark gray glass manufacturer based on sheet glass and float glass technology. In an effort to meet market demand, the company has committed to improving product quality and quantity. However, the company is facing a decline in managerial performance, allegedly caused by suboptimal decentralization, unclear assignments, and weak organizational commitment. This condition has the potential to hinder the achievement of operational targets and the company's overall strategy. The purpose of this study was to determine the impact of decentralization, task uncertainty, and organizational commitment partially on managerial performance and to determine whether the management accounting system strengthens the impact of decentralization, task uncertainty and organizational commitment partially on managerial performance. The population in this study were all employees working at PT. Real Glass Semarang totaling 100 people. The number of samples taken in this study was determined through the census method, by taking a sample of 100 people or the total population. The data analysis techniques used were Multiple Linear Regression and Moderated Regression Analysis (MRA). Data analysis showed that decentralization, task uncertainty and organizational commitment partially had a significant positive impact on managerial performance, and the management accounting system strengthened the impact of decentralization and organizational commitment partially on managerial performance, but the management accounting system weakened the effect of task uncertainty on managerial performance. Keywords: Decentralization, Task Uncertainty, Organizational Commitment, Management Accounting Systems, Managerial Performance